Investigating the genetic architecture of dementia with Lewy bodies: a two-stage genome-wide association study. Issue 1 (January 2018) - Guerreiro, Rita; Ross, Owen A; Kun-Rodrigues, Celia; Hernandez, Dena G; Orme, Tatiana; Eicher, John D; Shepherd, Claire E; Parkkinen, Laura; Darwent, Lee; Heckman, Michael G; Scholz, Sonja W; Troncoso, Juan C; et al.
Summary: Background: Dementia with Lewy bodies is the second most common form of dementia in elderly people but has been overshadowed in the research field, partly because of similarities between dementia with Lewy bodies, Parkinson's disease, and Alzheimer's disease. So far, to our knowledge, no large-scale genetic study of dementia with Lewy bodies has been done. To better understand the genetic basis of dementia with Lewy bodies, we have done a genome-wide association study with the aim of identifying genetic risk factors for this disorder. Methods: In this two-stage genome-wide association study, we collected samples from white participants of European ancestry who had been diagnosed with dementia with Lewy bodies according to established clinical or pathological criteria. In the discovery stage (with the case cohort recruited from 22 centres in ten countries and the controls derived from two publicly available database of Genotypes and Phenotypes studies [phs000404.v1.p1 and phs000982.v1.p1] in the USA), we performed genotyping and exploited the recently established Haplotype Reference Consortium panel as the basis for imputation. Pathological samples were ascertained following autopsy in each individual brain bank, whereas clinical samples were collected after participant examination. There was no specific timeframe for collection of samples. We did association analyses in all participants with dementia with Lewy bodies, and also only in participants with pathological diagnosis. In the replication stage, we performed genotyping of significant and suggestive results from the discovery stage. Lastly, we did a meta-analysis of both stages under a fixed-effects model and used logistic regression to test for association in each stage. Findings: This study included 1743 patients with dementia with Lewy bodies (1324 with pathological diagnosis) and 4454 controls (1216 patients with dementia with Lewy bodies vs 3791 controls in the discovery stage; 527 vs 663 in the replication stage). Results confirm previously reported associations: APOE (rs429358; odds ratio [OR] 2·40, 95% CI 2·14–2·70; p=1·05 × 10 −48 ), SNCA (rs7681440; OR 0·73, 0·66–0·81; p=6·39 × 10 −10 ), an GBA (rs35749011; OR 2·55, 1·88–3·46; p=1·78 × 10 −9 ). They also provide some evidence for a novel candidate locus, namely CNTN1 (rs7314908; OR 1·51, 1·27–1·79; p=2·32 × 10 −6 ); further replication will be important. Additionally, we estimate the heritable component of dementia with Lewy bodies to be about 36%. Interpretation: Despite the small sample size for a genome-wide association study, and acknowledging the potential biases from ascertaining samples from multiple locations, we present the most comprehensive and well powered genetic study in dementia with Lewy bodies so far. These data show that common genetic variability has a role in the disease. Funding: The Alzheimer's Society and the Lewy Body Society.